Aida Chocs Enterprise / Noranisya Nasaruddin - Nasaruddin, Noranisya (2021)
Nowadays people living in Malaysia, as well as visitors eat much same kinds of food as are eaten in many other countries in Europe, North America and Asia. Chocolates and cookies is also a famous food. Basically, chocolate is made from cocoa beans and so on. Based on Malaysia population people it is a high potential to doing business of chocolates and cookies. So, Puan Zuraidah Bt Saidon who was born on 24 April 1972nin Kedah, Malaysia take this opportunity to expand her enthusiasm by build and operated a company that calls Aida Chocs Enterprise which is promote and severed a local chocolate and cookies. She is entrepreneur in SME industry. Before she become the owner of this company, she was working as a clerk for AM Bank Group and involve as part-time by selling cookies, bakery and chocolates at Batu Uban, Penang and at area fair. Aida Chocs Enterprise establishes on 12 June 2007 but its really operation full time on early 2009 at D9 Medan Suri Sg. Nibong Besar Pulau Pinang. In the first year, when Aida Chocs Enterprise was operated, this company achieved RM 9700 revue profit to an accomplishment to be proud of. They make their history where this company become the first of newly SME won awards as Malaysian Good Design in 2009 and Marble Orange Cookies also Sweet Paradise Chocolate has been awarded as Malaysia Good Design in 2009. This company also recognized as one of the Quality Malaysian Product and it bears unique products characteristic. Move over, this company carry the HACCP and HALAL certification, making Aida Chocs Enterprise a beverage that can be enjoy by all people and all ages.